29-6x=-31-2x

Simple and best practice solution for 29-6x=-31-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 29-6x=-31-2x equation:


Simplifying
29 + -6x = -31 + -2x

Solving
29 + -6x = -31 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
29 + -6x + 2x = -31 + -2x + 2x

Combine like terms: -6x + 2x = -4x
29 + -4x = -31 + -2x + 2x

Combine like terms: -2x + 2x = 0
29 + -4x = -31 + 0
29 + -4x = -31

Add '-29' to each side of the equation.
29 + -29 + -4x = -31 + -29

Combine like terms: 29 + -29 = 0
0 + -4x = -31 + -29
-4x = -31 + -29

Combine like terms: -31 + -29 = -60
-4x = -60

Divide each side by '-4'.
x = 15

Simplifying
x = 15

See similar equations:

| 2y=128whatisy | | 6m-4m=16 | | 5x+4(-2x-4)=8 | | 234=(.8)x | | 0=-7r-3 | | -10x+3x^2+3=0 | | 3x+8(3-x)=4 | | c^19*c^5= | | 2(6)+2(W)=72 | | 111=12x-5 | | Y=x^5-7x^3-18 | | t-9=20 | | -16=x+8+7x | | 130x+210=1000 | | 23-x=19+11 | | 7=-1+11u | | -4-7r=-39 | | 234(.8)=x | | -3y+4=6x-5 | | -4(6-2p)= | | (3x^2+26x-64)=0 | | 18+(-7)= | | 7(5r+1)=-238 | | 15y^2-33y+18=0 | | 150=-3(-2+8x) | | 3(2x+1)-4(2x-4)=0 | | 150t=3 | | 7d-d+4d+9-5d=0 | | 234=(.2)(x) | | (3x^2+26x+64)=0 | | 2N-10=2N+20 | | ax=3a-y |

Equations solver categories